2010
DOI: 10.5194/angeo-28-1101-2010
|View full text |Cite
|
Sign up to set email alerts
|

On the seasonal dependence of relativistic electron fluxes

Abstract: Abstract. The nature of the seasonal dependence of relativistic electron fluxes in the Earth's outer zone is investigated using 11 years of data from sensors onboard the SAMPEX spacecraft. It is found that, the relativistic electron fluxes show a strong semiannual modulation. However, the highest electron fluxes occur at times well away from the nominal equinoxes, lagging them by about 30 days. The time lag also shows a solar cycle phase dependence for the peak fluxes. The electron peak fluxes lag the vernal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
3
14
1
4
Order By: Relevance
“…These results differ from previous ones reported in (Kanekal et al, 2010). Analyzing SAMPEX electron flux data, they found a more prominent role for the RM effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from previous ones reported in (Kanekal et al, 2010). Analyzing SAMPEX electron flux data, they found a more prominent role for the RM effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Note that if the peaks and valleys times expected for the equinoctial mechanism are shifted forward 4 days as in (Kanekal et al, 2010), the fluence times of maxima/minima fall into the equinoctial uncertainty interval. This time shift was attributed by Li et al (2001) and Kanekal et al (2010) to finite solar wind speed (∼ 440 km s −1 ).…”
Section: Dates Of Maxima and Minimamentioning
confidence: 99%
See 1 more Smart Citation
“…The Russell-McPherron effect associates the seasonal variation with the variation of the angle between the geocentric solar magnetospheric (GSM) equatorial plane and the solar equatorial plane [Russell and McPherron, 1973]. None of the three main causes alone, or any combination of them, can explain completely the observed seasonal variation of magnetospheric storms [Häkkinen et al, 2003;Cliver et al, 2000] or radiation belt energetic electrons [Kanekal et al, 2010;Vassiliadis et al, 2002]. The complete set of processes causing the [27] We found the largest number of substorms in winter during the declining solar cycle phase, the longest substorms in summer during sunspot maxima, and the most intense substorms in spring and fall during the declining solar cycle phase.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by Fidani et al (2008) where the selected EBs from NOAA satellite time series exhibited peak values between May and August annually, while less markedly in December. Annual (Vassiliadis et al, 2002) and semiannual (Kanekal et al, 2010) modulations in electron flux were observed in the SAMPEX data, where northern summer and spring with autumn flux increased, respectively. The SAMPEX lowEarth polar orbit at an altitude of about 600 km and an inclination of 82 • (Baker et al, 1993) was similar to the DEME-TER orbit.…”
Section: Long-term Variation Features Of Ebs At Different Energy Bandsmentioning
confidence: 97%